Music and ethical responsibility - Warren, Jeff R. 1977- (Cambridge University Press, 2014)
Discussions surrounding music and ethical responsibility bring to mind arguments about legal ownership and purchase. Yet the many ways in which we experience music with others are usually overlooked. Musical experience and practice always involve relationships with other people, which can place limitations on how we listen to and act upon music. In Music and Ethical Responsibility, Jeff Warren challenges current approaches to music and ethics, drawing upon philosopher Emmanuel Levinas's theory that ethics is the responsibilities that arise from our encounters with other people. Warren examines ethical responsibilities in musical experiences including performing other people's music, noise, negotiating musical meaning, and improvisation. Revealing the diverse roles that music plays in the experience of encountering others, Warren argues that musicians, researchers, and listeners should place ethical responsibility at the heart of musical practices